If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 78 = -5(3x + 6) + 2x Reorder the terms: 78 = -5(6 + 3x) + 2x 78 = (6 * -5 + 3x * -5) + 2x 78 = (-30 + -15x) + 2x Combine like terms: -15x + 2x = -13x 78 = -30 + -13x Solving 78 = -30 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. 78 + 13x = -30 + -13x + 13x Combine like terms: -13x + 13x = 0 78 + 13x = -30 + 0 78 + 13x = -30 Add '-78' to each side of the equation. 78 + -78 + 13x = -30 + -78 Combine like terms: 78 + -78 = 0 0 + 13x = -30 + -78 13x = -30 + -78 Combine like terms: -30 + -78 = -108 13x = -108 Divide each side by '13'. x = -8.307692308 Simplifying x = -8.307692308
| 0=-5x^2+5x+3 | | 5/4y^2-625/36y-275/36 | | 4(x+10)=3x-10+2x+20 | | x-2(2x-2)=3y+5 | | 2x-10y=-34 | | 15x^3+38x^2-23x-6=(5x+1)(x+3)l | | 6+5(-2)-2y=0 | | 6+5x-2(-4-x)=0 | | 1000x+(-45)y=x+y | | -4(-1)-7y=18 | | -4(0)-y=-3 | | x+x+x=117 | | -2(1)+4y=10 | | -5(-3)-4y=23 | | (24x+2)+6=42 | | 4(7)+2y=20 | | (24+2)+6=42 | | 5x+7y=27 | | 7(1)+6y=-11 | | 5(4-3x)+17=-3(7+8x)-7 | | -2(2)-y=11 | | -4(0)-y=12 | | (24x+2)+4=46 | | 12(0)-2y=-14 | | (26x+3)+56=45 | | -24(0)-3y=1 | | -3-4y=-5 | | -2(-4.5)+2y=-10 | | 7(-4)-4y=-16 | | (12c^10)/(4c^14) | | 4(0)+2y=-4 | | x-4/5=-1/5 |